2015
DOI: 10.1016/j.eats.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Reconstruction of the Medial Patellofemoral Ligament Using the Fascia Lata as an Autograft

Abstract: The medial patellofemoral ligament (MPFL) ensures stability of the patella against lateral forces. In cases of recurrent lateral patellar luxation, surgical reconstruction of the MPFL has an important role in treating lateral patellar instability. Several biomechanical studies have presented valuable pieces of information about various techniques for re-creating this medial patellofemoral complex mainly using the gracilis tendon as an autograft. However, with the increasing number of MPFL reconstructions, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“… 2 Although an “à la carte” plan based on reconstructing all anatomic disorders that may contribute to patellofemoral instability has been advocated, a standard surgical technique to treat this condition remains to be seen. 3 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 2 Although an “à la carte” plan based on reconstructing all anatomic disorders that may contribute to patellofemoral instability has been advocated, a standard surgical technique to treat this condition remains to be seen. 3 …”
mentioning
confidence: 99%
“…They vary in terms of graft choice, patellar and femoral attachments, type of fixation, and graft tension at the time of fixation. 2 , 3 , 6 , 7 , 8 The graft attachments both at the patellar site and at the femoral site are one of the most discussed issues as they are probably the main causes of complications after MPFL reconstruction. 9 The aim of the current work is to present an implant-free, simple, and reproducible method for MPFL reconstruction technique that is not based on radiologic landmarks.…”
mentioning
confidence: 99%
“…9 In a randomized controlled trial comparing nonoperative treatment vs MPFL reconstruction, Bitar et al found significantly greater Kujala scores and fewer recurrences/subluxations in the reconstruction group. 10 Many surgical techniques for MPFL reconstruction have been described, [11][12][13][14][15][16][17][18][19] but no single technique has been proven to be significantly superior to the others. The choice of technique may be guided by the complications associated with different techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these are employed in patients with skeletal immaturity, high riding patella, trochlear dysplasia, and ligament hyperlaxity (14). They vary in terms of graft choice, type of fixation, patellar and femoral attachments and graft tension at the time of fixation (13,(15)(16)(17). A standard surgical technique to manage this condition remains elusive (15).…”
Section: Introductionmentioning
confidence: 99%
“…They vary in terms of graft choice, type of fixation, patellar and femoral attachments and graft tension at the time of fixation (13,(15)(16)(17). A standard surgical technique to manage this condition remains elusive (15). We present a simple and reproducible method for combined MPTL and MPFL reconstruction that is not based on radiographic landmarks and can be performed in skeletally immature patients.…”
Section: Introductionmentioning
confidence: 99%